2018
DOI: 10.1002/cpt.1103
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling for Olaparib Dosing Recommendations: Bridging Formulations, Drug Interactions, and Patient Populations

Abstract: We report physiologically based pharmacokinetic-modeling analyses to determine olaparib (tablet or capsule) drug-drug interactions (DDIs). Verified DDI simulations provided dose recommendations for olaparib coadministration with clinically relevant CYP3A4 modulators to eliminate potential risk to patient safety or olaparib efficacy. When olaparib is given with strong/moderate CYP3A inhibitors, the dose should be reduced to 100/150 mg b.i.d. (tablet), and 150/200 mg b.i.d. (capsule). Olaparib administration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
(106 reference statements)
1
41
0
Order By: Relevance
“…In this study, we found a 13% increase and 13% decrease in olaparib C max and a 15% and 8% increase in olaparib AUC seen in patients with mild or moderate hepatic impairment, respectively, vs those with normal hepatic function; these variations in olaparib exposure were not considered clinically relevant 19,20 . Variation in olaparib exposure was notable in the moderate hepatic impairment group; however, this was largely because of 1 patient who had increased exposure to olaparib (indicated by AUC 0–t and C max values; see the Supplementary Materials for further information on this patient).…”
Section: Discussionmentioning
confidence: 66%
“…In this study, we found a 13% increase and 13% decrease in olaparib C max and a 15% and 8% increase in olaparib AUC seen in patients with mild or moderate hepatic impairment, respectively, vs those with normal hepatic function; these variations in olaparib exposure were not considered clinically relevant 19,20 . Variation in olaparib exposure was notable in the moderate hepatic impairment group; however, this was largely because of 1 patient who had increased exposure to olaparib (indicated by AUC 0–t and C max values; see the Supplementary Materials for further information on this patient).…”
Section: Discussionmentioning
confidence: 66%
“…PBPK modeling has been widely used in drug development to support development decisions, pediatric dose selection, and regulatory submissions and labeling . In the current analysis, a PBPK model of acalabrutinib and its metabolite ACP‐5862 was developed by integrating physiochemical properties, in vitro metabolism data, and clinical PK results and was subsequently verified using available DDI clinical data and then applied to prospective predictions of acalabrutinib‐drug combinations for which no clinical data were available.…”
Section: Discussionmentioning
confidence: 99%
“…patients with cancer (and what type of cancer) or without cancer] included in these 14 studies were limited ( Figure 3 ). Of the remaining 10 drugs with a peer-reviewed publication describing dosing and/or pharmacokinetics according to the Child-Pugh criteria, only 3 drugs had studies in patients with cancer [HCC for lenvatinib 14 ; mixed tumor types (including ovarian cancer) for olaparib 15 , 16 ; solid tumors for osimertinib 17 ] ( Table 1 and Figure 3 ). Moreover, these peer-reviewed studies were all limited in enrollment size ( N ≤ 33 patients) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…2019;105:229-241. 15 Patient number: 23 patients (normal hepatic function, n = 13; Child-Pugh class A, n = 9; Child-Pugh class B results were ongoing at time of abstract publication) Patient characteristics: major tumor types included ovarian (17%), breast (13%), and colon (13%) with chronic hepatic impairment where liver metastases were not the sole reason for any changes in liver function Osimertinib For the treatment of patients with metastatic epidermal growth factor receptor T790M mutation positive non-small-cell lung cancer Grande et al. J Pharmacol Exp Ther .…”
Section: Resultsmentioning
confidence: 99%